Integrating mass spectrometry-based plasma (or serum) protein N-glycan profiling into the clinical practice? - Bruneel, Arnaud; Fenaille, François (Annals of Translational Medicine, 2019)
Congenital disorders of glycosylation (CDG) are clinically diverse inherited diseases affecting in particular the glycosylation of proteins. Since the first clinical description of CDGs in 1980 (1), a significant number of new CDG types have been reported with more than 130 today described (2). CDGs are rare essentially autosomal recessive disorders, with about 60% of them affecting protein N-glycosylation (3).